Multimedia Mobile Application of National Heroes History Learning for Children's Character Education - ANIS SUSILA ABADI; PIPIT FEBRIANA DEWI (Telematika, 2021)
Purpose: develope a multimedia application about the history of national heroes from Indonesia.Design/methodology/approach: the method used is the UCD (User Centered Design) method.Findings/result: this multimedia mobile application of national heroes history learning for children's character education has succeeded in meeting user needs.Originality/value/state of the art: a multimedia application about the history of national heroes from Indonesia.